PENGAWAS AN PEMBERIAN INSENTIF PAJAK PENGHASILAN FINAL BAGI PELAKU UMKM SAAT PANDEMI COVID-19 DI KANTOR PELAYANAN PAJAK PRATAMA BEKASI BARAT - Diana Prihadini; Krishantoro Krishantoro; Raka Aulia Diantoro; DWIKORA HARJO; Dani Milleano (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The COVID-19 pandemic that peaked in July 2020 has severely hit business actors in Indonesia, including Micro, Small and Medium Enterprises (MSMEs), which are business actors who dominate the economic cycle in this country as well as tax contributors. Many MSMEs have experienced a decline in sales, not even a few have gone bankrupt. The Directorate General of Taxes (DJP) is also thinking about the survival of MSMEs by issuing tax incentives for MSMEs. The implementation is not in line with the DJP's expectations because one of them is the lack of supervision from tax officers at the Tax Service Office, which are very inadequate in number. This phenomenon is raised in this study. The purpose of this study was to determine how optimal the supervision carried out by the DJP in the success of this program. The method used is descriptive qualitative. Data collection techniques by conducting observations, interviews with selected informants and documentation. The results showed that the supervision of this program did not run as expected. Many MSMEs do not take advantage of this incentive program, while those who follow it are not accompanied by compliance to report the realization of the program in accordance with existing regulations due to the complexity of the available applications and their lack of tax knowledge.